Study of the impacts of droplets deposited from the gas core onto a gas-sheared liquid film - Cherdantsev, Andrey V.; Hann, David B.; Hewakandamby, Buddhika N.; Azzopardi, Barry J. (Elsevier, 2016)
The results of an experimental study on droplet impactions in the flow of a gas-sheared liquid film are presented. In contrast to most similar studies, the impacting droplets were entrained from film surface by the gas stream. The measurements provide film thickness data, resolved in both longitudinal and transverse coordinates and in time together with the images of droplets above the interface and images of gas bubbles entrapped by liquid film. The parameters of impacting droplets were measured together with the local liquid film thickness. Two main scenarios of droplet-film interaction, based on type of film perturbation, are identified; the parameter identifying which scenario occurs is identified as the angle of impingement. At large angles an asymmetric crater appears on film surface; at shallow angles a long, narrow furrow appears. The most significant difference between the two scenarios is related to possible impact outcome: craters may lead to creation secondary droplets, whereas furrows are accompanied by entrapment of gas bubbles into the liquid film. In addition, occurrence of partial survival of impacting droplet is reported.